Microstructure and mechanical properties of a new Ni–Co based superalloy at intermediate temperatures - Zhongrun Xiao; Junyang He; Ji Gu; Bin Gan; Min Song (Journal of Materials Research and Technology, 2024)
Intermediate temperature embrittlement (ITE) is very common in Ni and Ni–Co based superalloys, which seriously restricts the application of these alloys. In this work, we developed a new Ni–Co based superalloy by increasing the content of Cr to eliminate ITE. The superalloy has a yield strength of ∼950 MPa in the intermediate temperature range (600–780 °C), while also maintain a tensile elongation of ∼15 %. Microstructural investigations showed that in the temperature range of 600–780 °C, the microstructure of the alloy consists of nano-sized L12 phase (γ′) distributing inside the γ matrix, and the deformation is dominated by anti-phase boundary (APB) shearing γ′ precipitates, which makes the yield strength of the alloy decrease only slightly at 600–780 °C (compared to that tested at room temperature). More importantly, the element Cr is enriched along the grain boundaries (GBs) to form a protective layer without the formation of brittle topologically close-packed (TCP) phases due to the inverse two-stage aging design. In addition, the formation of a discontinuous precipitation (DP) zone at the GBs can act as a stress buffer and introduce GB serrations to withstand intergranular cracking.